MOCVD growth and study of magnetic Co films; Surface Engineering; Vol. 32, iss.1 - Dorovskikh S. I. Svetlana Igorevna; Hairullin (Khayrullin) R. R. Rustam Ravilievich; Sysoev S. V. Sergey Viktorovich; Kriventsov V. V. Vladimir Vladimirovich; Panin A. V. Alexey Viktorovich; Shubin Yu. V. Yury Viktorovich; Morozova N. B. Nataljya Borisovna; Gelfond N. V. Nikolay Vasiljevich; Korenev S. V. Sergey Vasiljevich (2016, 2016)
Title screen